From Empathy to a Man into a Mystical Union with God - Machnacz, Jerzy (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
The philosophical thought of Edith Stein is connected with her life: life (praxis) asks the question to which she responds (theoria). Her philosophical work showsher personality (it is focused on searching for the sense of her own existence), being at thesame time personal (interested in a human being, at in discovering sense of our existence).Such à la Socrates philosophyseeksto comprehend life more thoroughly and thereby to change it. Stein’s way to herself starts with phenomenological empathy for (feeling-into) another man, with the intuition of another human being’s existence and with one’s own casual existence, and ends in a mystical unification with God, in the experienceof the fulfilment of one’s existence in the existence of God. The life and thoughtof Edith Stein – Saint Teresa Benedicta of the Cross are the testimony of searching for theTruth (theoria) and of being in the Truth (praxis).